Faktor-Faktor Predisposisi yang berhubungan dengan Pencegahan DBD di Tanjung Basung Wilayah Kerja Puskesmas Pasar Usang - Yulia M. Nur; Eliza Eliza; Windi Elsia Haria (Jurnal Akademika Baiturrahim Jambi, 2020)
Dengue fever is an infectious disease by a virus that is transmitted through the bite of the Aedes aegypti mosquito. Mild infections only cause patches on the body and mild flu symptoms. Dengue hemorrhagic fever is caused by dengue virus. Dengue hemorrhagic fever is not transmitted through human contact with humans. Predisposing factors encompass public knowledge and attitudes towards health, traditions and community trust in matters relating to health, the value system adopted by the community, education level, socio-economic level, and so on. This type of research is analytic descriptive with cross sectional method. The population in this study were patients who visited the health center totaling 25 people and a sample of 25 people taken by total sampling. Data collection tools using a questionnaire. Data analysis was carried out univariately and bivariately. The results of this study indicate that 64.0% of respondents have low knowledge, 52.0% of respondents have negative attitudes, 56.0% of respondents have bad actions, and 56.0% of respondents have low DHF prevention. There is a significant relationship between knowledge (0.013), attitude (0.003), action (0.010) with the prevention of DHF with p value 0.05. It is expected that respondents will maintain environmental hygiene by increasing their knowledge, attitudes and actions in preventing DHF by participating in DHF prevention activities.